Chinese-Ukrainian cooperation as a factor of energy security in Ukraine - Килимчук, Анна Анатоліївна (Київський національний університет імені Тараса Шевченка, 2015)
The purpose of the article The investigation and assessment of the economic advantages and disadvantages of Sino-Ukrainian energy projects, as well as the evaluation of the potential environmental risks of their introduction. Methodology covers the use of such methods as analysis and synthesis, as well as the method of systematization. Scientific novelty. The attempt to systematize the information on existing bilateral projects in the energy sector is implemented. The analysis of their viability and feasibility is given. Practical significance. The investigation and the following implementation of Chinese experience in the development of energy projects will provide an opportunity to diversify the sources of energy resources in Ukraine.

Мета. Дослідити та розкрити економічні переваги та недоліки китайсько-українських енергетичних проектів, а також потенційні екологічні ризики їх впровадження. Методика роботи охоплювала використання таких методів як аналіз і синтез, а також методу систематизації. Науковою новизна. Здійснено спробу систематизувати дані про існуючі двосторонні проекти в галузі енергетики, а також проведено аналіз їх перспективності та економічної доцільності. Практичне впровадження досвіду Китаю в галузі розвитку енергетичних проектів дасть змогу Україні диверсифікувати джерела енергетичних ресурсів.
Китайсько-українська співпраця як фактор енергетичної безпеки України
Keywords: energy security; alternative energy; coal gasification; the Sino-Ukrainian projects; енергетична безпека; альтернативна енергетика; газифікація вугілля; китайсько-українські проекти